Technology Utilization Training In Material Design Process, Learning Engagement & Learning Assessment For Senior High School Teachers - Dangin Dangin; Elysa Hartati (International Journal Of Community Service, 2022)
The use of technology is crucial to support effectiveness in the learning process. In this development trend, teachers are required to master and be able to use technology inside and outside the classroom or Teacher Pedagogical Content Knowledge (TPACK). This service program aims to answer the challenges faced by teachers at the high school level. Through training programs/workshops, teachers as participants are supposed to get knowledge about the use of technology in 3 learning processes, namely preparing materials (material design), attractive learning activities (learning engagement), and conducting evaluations or assessments.